2018
DOI: 10.35608/ruraled.v38i1.234
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration to Support Rural Student Social-Emotional Needs

Abstract: There is a growing emphasis in U.S. schools to focus on the social-emotional issues of rural students. Specifically, the effect of mental health issues on school success underscores the importance of collaboration between, and among, educators and specialized support personnel (SSP; e.g., school counselors). In rural areas, school counselors and school psychologists are positioned to assist students and their families to provide support within and surrounding the school environment. The purpose of this paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 60 publications
1
12
0
1
Order By: Relevance
“…Given that schools in rural areas are often community hubs, educational administrators often support the wellness needs of not only students but also the community (Clayton et al , 2010). Student support teams – including building principals, school counselors, social workers and school-based health care providers – often coordinate this work (Keeton et al , 2012; Michael and Jameson, 2017; Moore et al , 2005; Nichols et al , 2018). In this article, I focused on a group of communities and schools in rural northeastern Connecticut; I spent ten years in educational administration at a Regional Educational Service Center, or RESC, in the district.…”
Section: One District's Vision Of Success Through Wellnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that schools in rural areas are often community hubs, educational administrators often support the wellness needs of not only students but also the community (Clayton et al , 2010). Student support teams – including building principals, school counselors, social workers and school-based health care providers – often coordinate this work (Keeton et al , 2012; Michael and Jameson, 2017; Moore et al , 2005; Nichols et al , 2018). In this article, I focused on a group of communities and schools in rural northeastern Connecticut; I spent ten years in educational administration at a Regional Educational Service Center, or RESC, in the district.…”
Section: One District's Vision Of Success Through Wellnessmentioning
confidence: 99%
“…As the case presented in this article illustrates, critical leaders of place who engage with stakeholders in collaborative problem-posing, imagining and co-designing educational systems and programs that are more aligned with community values have a greater chance of establishing trust among community members. Critical leaders of place understand the importance of aligning the work of and within schools with the needs of the community, so that the schools, students, staff and community thrive through interdependence and commitment to efforts that are contextually designed to promote well-being, leverage strengths and address the challenges of rural schools and their community (Budge, 2006; Freire, 1970; Hoover and Mayworm, 2017; Nichols et al , 2018; Pendola and Fuller, 2018; Wagenfeld, 2003). Budge (2006) suggested that a critical view of leadership of place in rural contexts may be helpful in understanding not just the challenges but perhaps more importantly the strengths that rural communities possess.…”
Section: The Power Of Rural Placementioning
confidence: 99%
“…In summary, research exists addressing the role of school counselors in multiple crisis response situations (Allen et al, 2002;Riley & McDaniel, 2000), including school shootings (Fein, Carlisle, & Isaacson, 2008) and hostage events (Daniels, Bradley, & Cramer, 2007). Similarly, examples can be found in the literature addressing services school counselors can provide in response to various grief/loss-related situations (Guidry, Simpson, Test, & Bloomfield, 2013;Nichols, Goforth, Sacra, & Ahlers, 2017), such as parent/caregiver loss (Lenhardt & McCourt, 2000) and student suicide (Fineran, 2012), but we found no research specifically pertaining to school counselors' experiences of multiple student deaths in the same school year, or even specific to the death of one student. We conducted our study to begin to address this gap in the literature.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Schools play a significant role in addressing the mental health needs of students (Nichols, Goforth, Sacra, & Ahlers, 2017) and are the primary location of mental health services to support children's and adolescents' mental health needs. Thus, schools should be proud of the role they take on in the provision of mental health services and should not shy away from their role (Maag & Katsiyannis, 2010).…”
Section: Resultsmentioning
confidence: 99%